The Impact of Entrepreneurship on Project-risk Management According to the COSO System - Al-Rawashdeh , Abdullah Muhammad; AlHalaseh, Rula Hani (Jordan Journal of Business Administration, 2025)
This study aims to test the impact of entrepreneurship on the risk management of projects according to the COSO system in the projects of Jordanian electricity companies. The study population consisted of the Jordanian Electricity Distribution Company and the National Electricity Company. This study combines two highly important variables at present and was applied to companies from the energy sector, which is witnessing great interest from the whole world in the sustainability of its resources. To achieve the objective of the study, the deductive approach was adopted by designing an applied study that used quantitative analysis based on structural-equation modeling using the least squares method PLS-SEM. The sample size of the study was 68 individuals. A questionnaire was designed to collect the necessary data and distributed in a comprehensive-survey method. The response rate was 88.2%. The study reached a set of results; most notably: There is a significant effect of the creativity dimension in risk analysis and response to risks. The study recommended applying the study to other countries to increase the applicability of the research to other contexts.